Kemampuan Koneksi Matematis Siswa Dengan Self efficacy Tinggi Dalam Menyelesaikan Soal Cerita Matematika - Ulya, Aisyah Nuril; Nihayatus Sa'adah (Discovery, 2025)
Abstract: Mathematical connection ability is one of the essential aspects of learning mathematics because it enables students to relate mathematical concepts to one another as well as to real-life situations. However, some students still experience difficulties in connecting previously learned mathematical concepts with new ones. The results of the mathematical connection ability test show variations in students' scores, which are suspected to be influenced by differences in self-efficacy levels. This study aims to describe the mathematical connection ability of students with high self-efficacy. This research uses a qualitative approach with one ninth-grade student who has high self-efficacy as the subject. The results show that students with high self-efficacy are able to meet the three standards of mathematical connection ability: recognizing and using relationships among mathematical ideas, understanding the interconnections among mathematical concepts and building one idea upon another in an integrated manner, and recognizing and applying mathematical concepts outside the context of mathematics.